2021
DOI: 10.1128/msystems.00713-21
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Staphylococcus aureus SarA Regulon to Small RNAs

Abstract: Staphylococcus aureus , a commensal and opportunist pathogen, is responsible for a large number of human and animal infections, from benign to severe. Gene expression adaptation during infection requires a complex network of regulators, including transcriptional factors (TF) and sRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 104 publications
(200 reference statements)
0
7
0
Order By: Relevance
“…After excluding ribosomal and phage genes, we focused on genes expressed at twofold higher and or lower (Table 2). Genes regulated by SarA, ribosomal genes, phage, and transposon genes were excluded from the analysis (Manna et al, 2018; Oriol et al, 2021). In the Teg49 mutant, there were 22 genes that had notable transcriptional changes due to Teg49 independent of SarA when compared to the parental strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding ribosomal and phage genes, we focused on genes expressed at twofold higher and or lower (Table 2). Genes regulated by SarA, ribosomal genes, phage, and transposon genes were excluded from the analysis (Manna et al, 2018; Oriol et al, 2021). In the Teg49 mutant, there were 22 genes that had notable transcriptional changes due to Teg49 independent of SarA when compared to the parental strain.…”
Section: Resultsmentioning
confidence: 99%
“…RNA isolation and purification and subsequent Northern blot analysis were performed as described previously (Cheung et al, 1994; Manna et al, 2018; Oriol et al, 2021). Briefly, 15 μg of total RNAs were run on 8% polyacrylamide‐7 M urea gels and transferred onto Hybond‐N+ membranes (Amersham, USA) to detect sRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Those that regulate sRNA expression represent less than 10% of the TFs predicted (Table 4). Among them, the staphylococcal accessory regulator SarA is well studied and was shown to directly regulate 11 sRNAs, including RNAIII, Srn_3610_SprC, RsaD, and some sRNAs that are part of the toxin-antitoxin system, such as SprG2 or SprA2 AS [86,[186][187][188]. In their recent study, Oriol and colleagues combined the use of ChIPseq and RNA-Seq to conclude that the SarA sRNA regulon may encompass 51 sRNAs [188].…”
Section: Transcription Factors and Their Srna Regulonsmentioning
confidence: 99%
“…Among them, the staphylococcal accessory regulator SarA is well studied and was shown to directly regulate 11 sRNAs, including RNAIII, Srn_3610_SprC, RsaD, and some sRNAs that are part of the toxin-antitoxin system, such as SprG2 or SprA2 AS [86,[186][187][188]. In their recent study, Oriol and colleagues combined the use of ChIPseq and RNA-Seq to conclude that the SarA sRNA regulon may encompass 51 sRNAs [188]. Although some of them may not be direct targets, it is possible that the number of direct sRNA targets is underestimated.…”
Section: Transcription Factors and Their Srna Regulonsmentioning
confidence: 99%
“…SarA, a well-known S. aureus regulatory system, regulates the expression of many important virulence factors and induces S. aureus to produce biofilms, mainly by inhibiting the secretion of proteases ( Trotonda et al, 2005 ; Abdelhady et al, 2014 ). It has been reported that not only is the biofilm-forming ability of sarA mutants seriously damaged but it also leads to changes in the expression levels of at least 120 genes ( Mauro et al, 2016 ; Oriol et al, 2021 ). Numerous natural compounds, including thymol, carvacrol, and hesperidin, have been found to combat MRSA biofilms by targeting SarA ( Selvaraj et al, 2020 ; Yuan et al, 2020 ; Vijayakumar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%